Pengembangan LAPD berorientasi PBL untuk Melatihkan Kemampuan Berpikir Kritis Peserta Didik Pada Materi Larutan Penyangga - Aurelsa, Febrina Reva; Yonata, Bertha (PendIPA Journal of Science Education, 2026)
This study was conducted to analyze the feasibility of PBL-based LAPD in developing critical thinking skills in Phase F of buffer solution material. The feasibility of LAPD was evaluated based on the aspects of validity, practicality, and effectiveness. The research design applied was Research and Development (R&D) with the 4D Thiagarajan development model, which includes definition, design, and development. Limited-scale testing was applied to grade XI students at Widya Darma High School in Surabaya. The feasibility analysis of LAPD in terms of content validity, construct validity, and graphic validity showed a mode score of 5, which is classified as very good. The practicality of the LAPD was proven by a student response rate of 90% and an activity observation result of 93.30%, thus classified as very practical. The effectiveness aspect was determined based on the pretest and posttest critical thinking scores. Testing with the paired t-test method obtained a right-hand p-value of 0.000 (<0.05), so the alternative hypothesis H1 was accepted and H0 was rejected. This improvement was supported by a critical thinking N-gain value of 0.77 in the high category, as well as student learning outcomes of 87.5, which had reached mastery. The analysis results indicate that PBL-oriented LAPD is feasible to be applied to train critical thinking on buffer solution material.